Indução Comportamental Molar e Posição Relativa dos Estímulos - SARMIENTO, Alejandra Rodríguez (Universidade Federal do Pará, 2019)
The concept of induction comprises a range of procedures that facilitate the occurrence of behavior. An aspect of induction already studied is the behavioral facilitation that a stimulus produces when paired regularly with another stimulus, a process that might explain the spread of effect traditionally attributed to operant reinforcement. The aim of the present project was to evaluate the effect of the relative position of stimuli on response induction in the absence of reinforcement. Two experiments were run, each with 20 subjects distributed randomly in two groups. The subject's task consisted of observing a list of 16 words always with the same order, followed by a test period with the same list except a target word (“reinforcement”) that the subject was supposed to make appear on the screen by clicking on the other words. This task was repeated six times. In Experiment 1, each group had the target word located in different positions. The results suggest more response induction in stimuli close to the target stimulus. The purpose of Experiment 2 was to evaluate whether the results of Experiment 1 were due to serial position or the correlation between the target word and neighboring words. The task was the same, except that for one of the groups the position of neighboring words was changed during testing. The results are indicative of a process of bidirectional response induction for the stimuli close to the target stimulus, which is consistent with the hypothesis that the spread of effect arises from stimulus-function facilitation.